Psychiatric nursing - Keltner, Norman L.; Schwecke, Lee Hilyard;Bostrom, Carol E. (St. Louis, Missouri : Mosby Elsevier, 2007)
Psychiatric Nursing, 5th Edition focuses on the therapeutic skills needed by a psychiatric nurse. The psychotherapeutic management model emphasizes a three-pronged approach to psychiatric nursing provides the framework for the book and is presented clearly and understandably. The model takes a practical, clinical approach to nursing by integrating clinical realities with the theory taught in nursing schools, emphasizing those duties for which nurses are primarily responsible. A separate unit on the continuum of care discusses care settings and case management. An entire unit on pharmacology includes drug side effects, nursing interventions, and a new chapter on antidementia drugs. Each chapter begins with learning objectives to point students toward important concepts. Case studies in selected chapters help the student conceptualize the development of effective nursing care strategies. Includes family issues boxes in selected chapters that highlight the issues families must confront when a member suffers from mental illness. Includes clinical examples in the form of concise vignettes drawn from the authors' own experience to provide realistic illustrations of specific content. New chapter on antidementia drugs provides up-to-date information on psychopharmacology for antidementia disorders. Updated DSM-IV-TR content based on the latest text revision. Putting It All Together headings identify the end-of-chapter psychopathology summary in each of the clinical chapters. Norm's Notes, a direct student-to-author communication in the form of a post-it note, offers helpful tips for understanding difficult topics. Highlighting the Evidence boxes feature summarized research articles that demonstrate the effects of research on today's practice.
Contents: Introduction to psychiatric nursing -- Psychotherapeutic management in the continuum of care -- Continuum of care -- Models for working with psychiatric patients -- Legal issues -- Psychobiologic bases of behavior -- Nurse-patient communication -- Nurse-patient relationship -- Nursing process -- Stress, anxiety, coping, and crisis -- Working with the aggressive patient -- Working with groups of patients -- Working with the family -- Cultural competence in psychiatric nursing -- Spirituality -- Introduction to psychotropic drugs -- Antiparkinsonian drugs -- Antipsychotic drugs -- Antidepressant drugs -- Antimanic drugs -- Antianxiety drugs -- Antidementia drugs -- Introduction to milieu management -- Variables affecting the therapeutic environment -- Therapeutic environment in various treatment settings -- Special environments: forensic psychiatric treatment settings -- Introduction to psychopathology -- Schizophrenia and other psychoses -- Depression -- Bipolar disorders -- Anxiety-related, somatoform, and dissociative disorders -- Cognitive disorders -- Personality disorders -- Sexual disorders -- Substance-related disorders -- Dual diagnosis -- Eating disorders -- Behavior therapies -- Somatic therapies -- Alternative and complementary therapies -- Survivors of violence and trauma -- Child and adolescent psychiatric nursing -- Mental disorders in older adults.
Includes bibliographical references and index.
Keywords: PSYCHIATRIC NURSING